The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/hep.26019
|View full text |Cite|
|
Sign up to set email alerts
|

Deficiency of G-protein-coupled bile acid receptor Gpbar1 (TGR5) enhances chemically induced liver carcinogenesis

Abstract: Gpbar1 (TGR5), a membrane-bound bile acid receptor, is well known for its roles in regulation of energy homeostasis and glucose metabolism. We recently reported that TGR5 activation inhibits nuclear factor κB (NF-κB)-mediated inflammation. Here we show that TGR5 deficiency enhances chemically-induced liver carcinogenesis, and that TGR5 is a negative regulator of signal transducer and activator of transcription 3 (STAT3) signaling. Mice lacking TGR5 were much more susceptible to diethylnitrosamine (DEN)-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 44 publications
(60 reference statements)
0
27
0
Order By: Relevance
“…72 Loss of TGR5 in mice also increased susceptibility to diethylnitrosamine-induced acute liver injury and cancer due to increased hepatocyte death, compensatory proliferation, and expression of inflammatory cytokines. 73 Moreover, TGR5 KO mice displayed abnormal hydrophobic BA composition, severe hepatocyte necrosis, prolonged cholestasis, exacerbated inflammatory response, and delayed regeneration compared to WT mice post partial hepatectomy. 74 Treatment of non-alcoholic fatty liver disease (NAFLD) mice with dual FXR/TGR5 agonist decreased intrahepatic inflammation and improved histological features.…”
Section: Ba Related Molecular Playersmentioning
confidence: 99%
“…72 Loss of TGR5 in mice also increased susceptibility to diethylnitrosamine-induced acute liver injury and cancer due to increased hepatocyte death, compensatory proliferation, and expression of inflammatory cytokines. 73 Moreover, TGR5 KO mice displayed abnormal hydrophobic BA composition, severe hepatocyte necrosis, prolonged cholestasis, exacerbated inflammatory response, and delayed regeneration compared to WT mice post partial hepatectomy. 74 Treatment of non-alcoholic fatty liver disease (NAFLD) mice with dual FXR/TGR5 agonist decreased intrahepatic inflammation and improved histological features.…”
Section: Ba Related Molecular Playersmentioning
confidence: 99%
“…We conducted TGR5 overexpression under normal and high glucose levels and found that, without exogenous stimulation, overexpression of TGR5 decreased FN, ICAM-1, and TGF-β1 protein contents (Figs.3B-3E). TGR5 showed receptor activity without ligand binding, which could be related to TGR5 constitutive activity [13,28].…”
Section: Tgr5 Overexpression Inhibited High Glucose-induced Fn Icam-mentioning
confidence: 98%
“…Animal studies show that activation of this receptor inhibits inflammatory processes55–57 and minimises associated liver injury. It may also have a protective role in carcinogenesis of the liver 58. Fibroblast growth factor 19 (FGF19) has also been discovered as a therapeutic target for patients with PBC.…”
Section: Investigational Therapiesmentioning
confidence: 99%